MATHEMATICAL MODEL OF HEADRIG PRINCIPAL MOVEMENT DRIVE - Dmitry O. Kozyrev; Arine A. Avakyan (Advanced Engineering Research, 2012)
The dynamic characteristics of the mechanical operation are analyzed. The mathematical model of the drive of the power-saw bench principal movement is built.